The impact of the National Service Programme on self-resilience among youth in Malaysia - Abd Manaf, Norsyahrina; Abu Samah, Bahaman; Ahmad, Nobaya (Universiti Putra Malaysia Press, 2013)
Physical activities, besides having a positive impact on health, are also effective in improving strength, bravery and resilience in individuals. In Malaysia, there are a number of physical programmes designed with this objective in mind such as the National Service Programme. Compared with other physical programmes, the physical module in the National Service Programme is quite different due to its longer duration. The main objective of the physical module in the National Service Programme is to enhance self-resilience among the trainees; this study aims to discover the effectiveness of such a module in enhancing self-resilience among the participants and attempts to provide answers to these main questions: How much self-resilience is gained by the trainees? Is there any difference in their self-resilience before and after they joined the physical training module? This is a quantitative study in which a total of 362 trainees were selected based on multi-stage sampling. The data collection process covered two stages (pre- and post).Based on the analysis done, it was found that most of the trainees had a moderate level of self-resilience in the pre- and post test. The results demonstrated that the physical module was able to enhance the trainees’ self-resilience based on the significant difference identified in the mean score of the pre- and post tests. It is therefore recommended that the National Service Programme in Malaysia be implemented for a longer period of time and that the period for physical training be extended to give more room for new and challenging activities.